2022
DOI: 10.1109/mra.2021.3138388
|View full text |Cite
|
Sign up to set email alerts
|

Damping in Compliant Actuation: A Review

Abstract: This article has been accepted for inclusion in a future issue of this journal. Content is final as presented, with the exception of pagination.C ompliant actuator technology aims at building robots capable of physically interacting with humans and the environment, matching the versatility and capacity of biological systems. Recently, it underwent a significant evolution with the introduction of damping to improve performance. Such development reflects several aspects, including energy saving and oscillation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“… 41 , 42 , is carried by the force–velocity relation, and whether a trade-off exists between the force–velocity relation’s stabilizing effect and control effort. From a technical perspective, understanding low-level control of the force–velocity relation can promote bio-inspired designs for assistive robotic devices, as numerous studies have suggested that implementing (tunable) dampers can improve the system performance and facilitate robustness against external perturbations 17 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 , is carried by the force–velocity relation, and whether a trade-off exists between the force–velocity relation’s stabilizing effect and control effort. From a technical perspective, understanding low-level control of the force–velocity relation can promote bio-inspired designs for assistive robotic devices, as numerous studies have suggested that implementing (tunable) dampers can improve the system performance and facilitate robustness against external perturbations 17 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the activation of the damping pipe results in distinct profiles for the true damping B s due to varying pressures. This means that the damping constant B c contained within the spring will change relative to the pressure that inflatable pipes exert, as shown in (2). Additionally, the distance d p between the damping pipes and spring helical lines is interpreted to accurately track the effect of damping on double-sided spring.…”
Section: A Mechanism Designmentioning
confidence: 99%
“…However, conventional electric motors have limitations when it comes to tasks that require flexibility, energy efficiency, and safe interaction with the load side. For example, achieving optimal robot locomotion requires a delicate balance of stiffness and damping [1], [2]. This challenge becomes particularly significant when actuators need to directly interact with humans, such as in manipulators for active task support [3]- [5] or as assistive mechanisms in human locomotion [6]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the demand for tunable damper is proposed. The variable damping actuators (VDAs) [25, 26] can change its physical damping to suppress the system oscillation. Laffranchi utilized a piezoelectric damper [26], which essentially operates as a friction damper by actively controlling friction force to mimic viscous damping effect.…”
Section: Introductionmentioning
confidence: 99%